Surrogate Modeling for Methane Dispersion Simulations Using Fourier Neural Operator - Zhang, Qie; Milletari, Micro; Oruganti, Yagna; Witte, Philipp (NeurIPS 2022 Workshop Tackling Climate Change with Machine Learning, 2022)
Methane leak detection and remediation are critical for tackling climate change, where methane dispersion simulations play an important role in emission source attribution. As 3D modeling of methane dispersion is often costly and time-consuming, we train a deep-learning-based surrogate model using the Fourier Neural Operator to learn the PDE solver in our study. Our preliminary result shows that our surrogate modeling provides a fast, accurate and cost-effective solution to methane dispersion simulations, thus reducing the cycle time of methane leak detection.
Proposal Track